2024
DOI: 10.1093/plcell/koae088
|View full text |Cite
|
Sign up to set email alerts
|

Plant enhancers exhibit both cooperative and additive interactions among their functional elements

Tobias Jores,
Jackson Tonnies,
Nicholas A Mueth
et al.

Abstract: Enhancers are cis-regulatory elements that shape gene expression in response to numerous developmental and environmental cues. In animals, several models have been proposed to explain how enhancers integrate the activity of multiple transcription factors. However, it remains largely unclear how plant enhancers integrate transcription factor activity. Here, we use Plant STARR-seq to characterize three light-responsive plant enhancers—AB80, Cab-1, and rbcS-E9—derived from genes associated with photosynthesis. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…With notable advances in high-throughput sequencing technologies, this presents an exciting opportunity to delve into the study of cis-elements in plants. In this issue, Tobias Jores, Jackson Tonnies, and colleagues ( Jores et al 2024 ) have provided an in-depth understanding of how 3 light-responsive enhancers function, both cooperatively and additively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…With notable advances in high-throughput sequencing technologies, this presents an exciting opportunity to delve into the study of cis-elements in plants. In this issue, Tobias Jores, Jackson Tonnies, and colleagues ( Jores et al 2024 ) have provided an in-depth understanding of how 3 light-responsive enhancers function, both cooperatively and additively.…”
mentioning
confidence: 99%
“…They demonstrated that these 3 enhancers exhibit light-responsive activity. Here, the same group of researchers, Tobias Jores, Jackson Tonnies, and colleagues ( Jores et al 2024 ) , aimed to interrogate these plant enhancers at nucleotide resolution. They divided each enhancer sequence into 5′ and 3′ fragments ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation